Physical and Mental Fatigue in Subjects Recovered from COVID-19 Infection: A Case–Control Study - Elanwar, Rehab; Hussein, Mona; Magdy, Rehab; Eid, Ragaey A; Yassien, Ahmed; Abdelsattar, Ahmed S; Alsharaway, Laila A; Fathy, Wael; Hassan, Amr; Kamal, Yasmine S (Neuropsychiatric disease and treatment, 2021)
Much effort has been directed toward studying COVID-19 symptoms; however, the post-COVID-19 phase remains mysterious. The aim of this work was to conduct a clinical and neurophysiological evaluation of physical and mental fatigue in COVID-19 long-haulers and to study whether markers of COVID-19 severity are able to predict the likelihood of developing postinfectious fatigue syndrome (PIFS) in such patients. This case-control study was conducted on 46 COVID-19 long-haulers who met the criteria for PIFS and 46 recovered COVID-19 subjects without any residuals. Clinical assessment of fatigue was done using a fatigue questionnaire. Repetitive nerve stimulation and single-fiber electromyography were done after excluding neuropathy and myopathy. The median value for physical fatigue was 4 (IQR 2-7), while that for mental fatigue was 2 (IQR 0-3). Each day's increase in the period of COVID-19 illness increased the odds of PIFS in COVID-19 long-haulers 1.104-fold, and each unit increase in ferritin increased the odds of PIFS 1.006-fold. A significant decrement in at least one muscle was observed in 50% of patients. Patients with PIFS had significantly higher mean consecutive difference (MCD) in the extensor digitorum communis than the control group. There were statistically significant positive correlations between MCD values and physical, mental, and total fatigue scores. Higher ferritin levels and prolonged COVID-19 infection were independent predictors of PIFS in COVID-19 long-haulers. There was electrophysiological evidence of abnormalities in the peripheral portion of the motor unit in COVID-19 long-haulers with PIFS.